ANALISIS MANAJEMEN PROGRAM KATERING MAKANAN SEHAT DALAM PEMENUHAN GIZI PAUD DI TK NEGERI PEMBINA 3 PEKANBARU - Duwi Yulianti; Yeni Solfiah; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The purpose of this research is to find out how the Management of the Healthy Food Catering Program is implemented well in Pembina 3 Public Kindergarten in Pekanbaru. This research is a qualitative descriptive study. The population of this research is the school, cooks and parents of TK Negeri Pembina 3 Pekanbaru. Data collection techniques used are through interviews, observation and documentation. Data analysis techniques in this study used data reduction, data presentation and drawing conclusions. The validity of the data used is the addition of persistence, observation persistence and triangulation. This research is a qualitative descriptive research, based on the results of interviews with school principals, teachers, cooks and parents of students that the implementation of healthy food counseling is going according to what is being guided from planning, organizing, organizing and evaluating everything has been going well so far. As for some things that are deemed inappropriate or in line with what was planned, the school will immediately repair them.Keywords: Catering Program Management